Regime-Switching Modelling of Globalization Analysis in the Context of Stock Markets under Sovereign Debt Crisis - Ferreira, N. B.; Menezes, R.; Mendes, D. A. (Finance and Economics Conference, 2011)
The internationalization of financial markets is one of the topics in the discussion about recent globalization trends. Other events such as the stock market crashes and financial crises also make the study of the globalization within international stock markets an important topic for financial policy makers. Several experimental research showed that stock markets display periods of marked turbulence and exhibit extreme values more often than one would expect if the series were normally distributed (fat tail property). In this context, in order to better understand this phenomenon, it was developed, between others, the Markov Switching Model (MSM). Nowadays, this kind of models has attached much attention in financial and economic modeling, since, ample empirical evidence has been gathered for both nonlinearity and structural changes in the dynamic properties of many observed time series. In particular, the dynamic behaviour of macroeconomic time series depends nonlinearly on the phase of the business cycle. This regime-switching behaviour related to expansion and contraction periods has been the focus of much research [see [1], [2], [3], [4]]. We focus our analysis to study mainly the effect of globalization on five international stock markets: (SP&500; FTSE100; NIKKEI100; IBEX35 and PSI20) based on daily closing stock market prices, from 1993 until 2010, employing a smooth transition regression (STAR) model.